Comparison the concepts of sense of place and attachment to place in architectural studies - Hashem, Hashemnezhad; Seyed Abbas, Yazdanfar; Ali Akbar, Heidari; Nazgol, Behdadfar (Faculty of Social Sciences and Humanities, UKM,Bangi, 2013)
Today, concepts such as place attachment, sense of place, meaning of place, place identity, and ... has devoted many studies In literature of architecture and urban design particularly in the field of environmental psychology. It is obvious that in all these concepts, various aspects of interaction between human and place and the impact that places have on people has been presented. This paper defines the concepts of sense of place and place attachment and explains the factors that affect them. Sense of place is a comprehensive concept which in it men feels places, percept them and attached meaning to them. Understanding the fundamental aspects of sense of place, can be effective in assess the level of public attachment to places and tendency of people to places. Place attachment refer to emotional and functional bonds between place and people which Interpreted in different scale from a district to a country in Environmental psychology. In this regard different studies point to varied of spatial and human factors. Review the literature, this paper achieves a comprehensive definition of these concepts and then it try to compare them to find their relationship. What will come eventually is that place attachment is one of the sense of place subsets. Thus in encounter of people and place if assume people sense of place a general feeling to that place, place attachment is a positive emotion which people have about the place.